Dissolution Stability study of Cefadroxil extemporaneous suspensions - González Vidal, Noelia Luján (2008)
Dissolution studies have become matter of great significance because, in most cases, drug dissolution is the rate-limiting step in the absorption process. As occurs with solid oral dosage forms, heterogeneous disperse systems (suspensions) could also have some problems with their in vitro dissolution. The dissolution behavior of four different brands of cefadroxil extemporaneous suspensions available in the Argentinian market was evaluated. The deliverable volume, pH, visual appearance, uniformity of dosage units, and assay were also studied. Powders for oral suspension were stored under different aging conditions. Samples at room temperature and refrigerated conditions were taken at several time points to carry out the dissolution stability study during the expiration period of the reconstituted form. Marked differences were recorded with respect to in vitro dissolution behavior between the different products under evaluation.